Perceptions of effective leadership in a medical school context - Bharwani, Aleem; Kline, Theresa; Patterson, Margaret (Canadian Medical Education Journal, 2019)
Background: There have been calls for the development of leadership attributes in healthcare practitioners through leadership development programs. However, understanding how leadership is conceptualized is needed to assure effective participant-centred leadership development programs. The purpose of this study was to elucidate how the construct of leadership is conceptualized by multiple stakeholder groups associated with medical school leadership programs. Methods: We conducted a total of 77 semi-structured interviews with six major demographic groups: Trainees (n= 16), Mid-Level University Leaders (n= 10), Clinician Leaders (n= 17), Senior University Leaders (n= 10), Medical Scientists (n= 12), and Senior Leaders, external to the University (n = 12) to address the research question. Results: Content analyses revealed that the leaders were expectedto create a compelling vision and a foster a motivating culture within the organization. Integrity and a sense of passion about leading were viewed as being principal characteristics of a leader. The twin skills of technical competence and communication were endorsed as most important for a leader. Finally, leaders are expected to be accountable for outcomes. Conclusion: Medical school leadershiptraining programs should strive to incorporate these characteristics, given their broad appeal to diverse interest groups.